(untitled) (Jurnal Ipteks Terapan, 2024)
This research aims to determine the effect of Return On Equity on stock prices, the effect of Return On Assets on stock prices, the effect of Current Ratio on Stock Prices, and the effect of Return On Equity, Return On Assets, and Current Ratio simultaneously on stock prices in period 4 year, namely 2018-2021. This research uses a quantitative approach with descriptive statistical analysis research type. The population in this study was 51 companies. This research uses financial report data with time series for the last 4 years published from www.idx.co.id. In this study, sample selection used the Purposive Sampling technique. The sample for this research was 33 companies in the last 4 year period with a total sample quantity of 132 Manufacturing Companies in the Consumer Goods Industry Sector. The results of this study indicate that partially Return On Assets and Current Ratio have no influence and are not significant on the share prices of manufacturing companies in the consumer goods industry sector. Partially, Return On Equity has a positive and significant influence on the share prices of manufacturing companies in the consumer goods industry sector. Meanwhile, the independent variables Return On Equity, Return On Assets and Current Ratio simultaneously have a significant effect on the dependent variable Share Prices of manufacturing companies in the consumer goods industry sector.